Tafahus faktor penarik dan pendorong yang mempengaruhi keputusan orang tua Memilih tempat studi untuk anaknya di Madrasah Ibtida’iyah Nurul Huda 2 Surodinawan Kota Mojokerto - Ihwan, Muhammad (Ta'dibia: Jurnal Ilmiah Pendidikan Agama Islam, 2016)
Loveliest child is a gift for a family that complements married life. Parents are obligated parties meet the child's needs, such as the child's need for affection, welfare, education and so forth. The problem in this research is generally Madrasah is the second choice for parents anaknyanya Choosing to study, but in fact at Madrasah Nurul Huda Ibtida'iyah 2 Surodinawan Mojokerto became the pride of the parents if their children are schooled in these institutions The purpose of this study first, know and analyze the push and pull factors that influence parents Decisions Choosing to his studies at Madrasah Nurul Huda Ibtida'iyah 2 Surodinawan Mojokerto. Second, find out and analyze which is the most dominant factor in the push and pull factors that influence parents Decisions Choosing to his studies at Madrasah Nurul Huda Ibtida'iyah 2 Surodinawan Mojokerto This study used a qualitative approach with a phenomenological study design. Data collected by way of interviews, observation, documentation. To obtain the validity of the data used measures perseverance observation and triangulation. Data analysis technique is done by means of data collection, data reduction, data presentation and conclusion. The findings showed that (1) Push and pull factors that influence parents Decisions Choosing to his studies at Madrasah Nurul Huda Ibtida'iyah 2 Surodinawan Mojokerto is a) Factors Psychology consists of motivation, perception, learning, beliefs and attitudes b) Social factors consisting of Group Reference / Reference, Family and the Role and Status c) Cultural factors decisive factor is religion and geographical regions. c) Personal factors which consists of Stages Age and the Life Cycle Works and State of Economy, Personality and Self-Concept and Lifestyle and Values ​​(2) Among the factors psychology, Social factors, and cultural factors Personal factors that most influence the decision of parents Choosing study for children in Madrasah Nurul Huda Ibtida'iyah 2 Surodinawan Mojokerto are psychological factors and personal factors.